The Microstructural Evolution of the Welded Joint of Super 304H Stainless Steel after 1000 Hours of Ageing at 700 and 750°C - T. Puszczało; H. Purzyńska; M. Sroka; K. Sówka; A. Zieliński (Archives of Metallurgy and Materials)
This study presents the results of microstructure and hardness tests of a homogenous welded joint made of Super 304H stainless steel after 1000 h of ageing at the temperature of 700 and 750°C. Super 304H steel is commonly used for high-pressure elements of modern power units for supercritical steam parameters. The article compares hardness with the microstructure images in the initial state and after ageing. The microstructure tests were carried out based on scanning microscopy, while the hardness tests were carried out on a stationary hardness tester in the HV10 scale. An increase in hardness after ageing was observed, which is directly related to the initiated precipitation process, both in the weld and base materials.